How is the Condition of Health Services at the UPT Puskesmas Griya Antapani Bandung City? - Kurniawati Kurniawati; Imanita Septian Rusdianti; Ginanjar Wira Saputra; Kornkanok Kanjanamethakul (Mahameru Publisher, 2023)
The purpose of this research is to identify and identify problems, obstacles, and efforts to overcome the quality of service at UPT Puskesmas Griya Antapani. Quality measurements in this study are responsiveness, reliability, assurance, empathy, tangibles. The research method in this research is descriptive analysis. Snow ball technique. The data collection technique is done by interviews and observation. The results of the research on the quality of immunization services at the UPT Puskesmas Griya Antapani are quite good but need to be optimized because there are still deficiencies, such as additional human resources, conventional data processing that needs to be computerized. From the results of interviews with informants, they felt that the quality of immunization services was good enough. It is suggested that the quality of immunization services in terms of responsiveness, reliability, assurance, empathy, tangibles needs to be looked at again for the progress of UPT Griya Antapani Health Center in terms of more optimal service.